Massive Scalar Field Evolution in the Dyadosphere Spacetime of Charged Black Hole - 王春艳 高亚军 (Communications in theoretical physics, 2013)
Scalar field quasinormal modes in the dyadosphere spacetime of charged black hole are studied by using the third-order WKB approximation. From numerical results obtained, we find that the scalar field mass u plays an important role in studying the quasinormal frequencies. With the scalar field mass increases, the real parts increase and the magnitudes of the imaginary parts decrease. Partieulary, these change are almost linearly.